Documentos sobre oficina de correo "Postmaster" de Manatí - Todd, Roberto H.; Córdova Dávila, Félix (My University, 1921)
Documentos sobre oficina de correo "Postmaster" de Manatí.
Keywords: Postal service--Puerto Rico.; Servicio postal--Puerto Rico.; Córdova Dávila, Félix, 1878-1938; López, Teodoro M.